Complaint Response Strategies in Interpersonally Sensitive Phone Interactions in Chinese Service - Liu, Ping; Cai, Min (Advances in Social Sciences Research Journal, 2020)
For any business organizations, it is of great importance to handle customer complaints effectively. This is particularly vital in the service industry as complaining customers are found not very collaborative and tend to be emotional in the process of complaining [1] and sometimes the exchanges between agents and complaining customers become interpersonally sensitive. Following Orthaber and Reiter’s [2] definition of “interpersonally sensitive exchange”, this study addresses two research questions: (1) what pragmatic strategies are employed by call center agents in interpersonally sensitive interactions in complaint responses? 2) and what are the effects of these strategies on interpersonal relationship in complaint responses? Based on a corpus of 42 outbound calls (approximately 7.5 hours) made by the agents in the Complaint Centre of one Chinese airline, four conventional and two unconventional complaint response strategies are found to be employed by the agents. These strategies produce positive outcomes in some cases while lead to opposite effects in others. An effective strategy can either enhance the rapport between the agent and the complaining customer, or benefit the progressivity of complaint handling. Conversely, it deteriorates the originally sensitive rapport and sometimes even leads to upgraded complaint.